ALLEGORICAL PORTRAIT OF PERSONAL IMAGE IN KOREAN LITERATURE. (On the example of Lim Je-je's The Condemned Mouse) - Elmuratova Umida Mamadiyarovna (International Journal of Literature and Language Studies, 2026)
This article is devoted to a scholarly analysis of allegorical art in the work “The Convicted Mouse” by one of the prominent representatives of Korean literature, Leem Jae. The study examines the artistic and aesthetic characteristics of the symbolic images created in the work, as well as their socio-philosophical significance. These images are interpreted not only as literary devices but also as representations of specific social strata, human character types, and various categories of individuals within society.